2021
DOI: 10.12688/wellcomeopenres.14709.3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of RRM domains and conserved aromatic residues in RGG motif  of eIF4G-binding translation repressor protein Sbp1

Abstract: Background: RNA binding proteins play crucial role in determining if a given mRNA will be translated, stored, or degraded. Sbp1 is an RGG-motif containing protein that is implicated in affecting mRNA decapping and translation. Sbp1 represses translation by binding eIF4G1 through its RGG-motif and activates decapping when overexpressed. In this report, we have assessed the genetic interaction of Sbp1 with decapping activators such as Dhh1, Pat1, and Scd6. We have further analyzed the importance of different dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The RRM is widely presented in eukaryotes and composed of two a-helices and four β-sheets. Bhatter et al [31] found that deletion of RRM domains compromised the ability of Sbp1 to induce growth defects in yeast by preventing localization of Sbp1 to RNA granules upon glucose starvation. Eulalio et al [32] showed that the RRM in GW182 protein contributes to miRNA-mediated gene silencing through protein-RNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…The RRM is widely presented in eukaryotes and composed of two a-helices and four β-sheets. Bhatter et al [31] found that deletion of RRM domains compromised the ability of Sbp1 to induce growth defects in yeast by preventing localization of Sbp1 to RNA granules upon glucose starvation. Eulalio et al [32] showed that the RRM in GW182 protein contributes to miRNA-mediated gene silencing through protein-RNA interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Complementation experiments presented in Fig. 4 were performed using endogenously tagged Edc3-mCherry-WT, and Edc3-mCherry Δsbp1 strains transformed with CEN plasmid (pRS315) expressing wild-type Sbp1-GFP or its mutants (Sbp1ΔRGG-GFP, Sbp1ΔRRM2-GFP, and Sbp1 ΔRRM1ΔRRM2-GFP) 59 .…”
Section: Methodsmentioning
confidence: 99%